If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -18 = 6 Reorder the terms: -18 + 4y = 6 Solving -18 + 4y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 4y = 6 + 18 Combine like terms: -18 + 18 = 0 0 + 4y = 6 + 18 4y = 6 + 18 Combine like terms: 6 + 18 = 24 4y = 24 Divide each side by '4'. y = 6 Simplifying y = 6
| 7(x-8)=35 | | A=2(x)(x)(x)+3(x)(x)+6 | | x^2+21x+10=0 | | 0.15(c+9)=0.9 | | x^5-2x^3-4x=0 | | -0.85(n+3)=3.4 | | -7y+14=-21 | | 6x-(11)-(7x)+12= | | 3(x-1)=-24 | | (49-3x)=(34-2x) | | 49-3x=34-2x | | 1.3x+-13=-5.2 | | 2c+4+3c=-36 | | 5x+15=22 | | 49-3x=3x-5 | | 7x-28=-14 | | 4(x+2)+x-11=2x-3+3(x+4) | | -3(9c+8)=26 | | (A+2)0.78=3.9 | | 4(90-x)+2=(180-x)+8 | | C=X^2-15x+50 | | 3(x+5)=x-10 | | 3535x-5725x+58y=4734z | | a/4-3/4=1/3 | | y^2-12y+27= | | X^5-4x^4+7x^3-10x^2+10x-4=0 | | A=(7x)(3x) | | -7x-3=13 | | 9.5=0.4(5x)+2.5 | | 9x+1=5x+15 | | 7*y-3=2*y-3 | | x^2-10x+25=x^2-8x+16+1 |